Analisa Performansi Clustering Routing Protocol Pada Wireless Sensor Network Untuk Aplikasi Kebakaran Hutan - Yasmin, Angreany; Anhar, Anhar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Forest fire is a problem that always occurr in the tropic areas when entering the dry season. To be able to anticipate forest fire early, it is necessary to have a remote detection system. WSN is one of systems that can detect and monitor forest fire remotely by placing node sensors on the location. In this application, there is a possibility that node sensors burned because of fire. This paper aims to investigate the performance of clustering routing protocol applied in WSN for forest fire application. There are three clustering routings analyzed; LEACH, LEACH-C and Modified LEACH.. Simulations were carried out using NS-2.35 software with measured parameters were throughput, packet loss, and energy consumed. The simulation results show that when the number of burn nodes increases, the throughput and packet loss of LEACH and LEACH decrease. Mean while , these performance index tend to stable in Modified LEACH. In term of energy consumed Modified LEACH the same pattern as in the throughput and packet loss. There is a significant in the number of energy consumed on LEACH-C in contrast, it rise slowly in LEACH.Keywords : Clustering Routing Protocol, WSN, Forest fire